PUBLIC PERCEPTIONS OF THE GREAT SEA WALL: A NETNOGRAPHIC STUDY ON PUBLIC BUDGETING, TRUST, AND RESISTANCE - Fahrudin Pasolo; Muhammad Ridhwansyah Pasolo; Zakaria Hatta; Abdul Rasyid (Universitas Airlangga, 2026)
The Great Sea Wall (GSW), valued at USD 80 billion and announced in 2025, sparked debate in Indonesia during fiscal austerity. This study fills a gap by examining TikTok citizen discourse on fiscal governance and legitimacy, areas rarely explored in accounting and public budgeting research. Data were collected from 1,568 comments on President Prabowo Subianto’s viral speech and filtered by likes and replies to capture the most resonant voices. Using manual thematic coding and NVivo visualization, four dominant themes emerged: concerns over budget efficiency, corruption, cynicism about policy continuity, and critiques of Java-centric development, with limited support framed around national pride and security considerations. Word-frequency analysis confirmed the centrality of fiscal terms such as “budget,” “corruption,” and “government.” Findings show that citizens evaluate megaprojects mainly through transparency, accountability, and distributive justice. This study contributes to public sector accounting and public budgeting literature by demonstrating how digital discourse functions as an informal arena of fiscal accountability and legitimacy assessment. The study concludes that integrating digital sentiment with performance-based budgeting, e-budgeting, and participatory oversight can strengthen fiscal legitimacy and restore citizen trust.